2002
DOI: 10.1269/jrr.43.353
|View full text |Cite
|
Sign up to set email alerts
|

p53 Dependency of Radio-adaptive Responses in Endogenous Spleen Colonies and Peripheral Blood-cell Counts in C57BL Mice

Abstract: Radio-adaptive responses at a conditioning X-ray dose of 0.45 Gy and a challenging dose of 5.0 Gy on hematopoietic indices were studied in C57BL mice with p53 (Trp53) wild, heterogenous and knockout allele. The conditioning irradiation, given 2 weeks before the challenging irradiation, induced radio-adaptive responses observed as a recovery of the peripheral blood-cell counts of leukocytes, thrombocytes and erythrocytes on day 14 after challenging irradiation in C57BL mice of the wild-type p53(+/+). The pre-ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…One study that did explicitly examine platelet levels found basal levels to be equivalent between p53 Ϫ/Ϫ and p53 ϩ/ϩ mice (14). However, systemic compensatory mechanisms could mask the effect of p53 on individual steps in Mk differentiation and maturation in steady-state animals.…”
Section: Cd8mentioning
confidence: 99%
“…One study that did explicitly examine platelet levels found basal levels to be equivalent between p53 Ϫ/Ϫ and p53 ϩ/ϩ mice (14). However, systemic compensatory mechanisms could mask the effect of p53 on individual steps in Mk differentiation and maturation in steady-state animals.…”
Section: Cd8mentioning
confidence: 99%
“…We previously showed that whole body pre-irradiation with 0.5 Gy of X-rays enhanced the survival of C57BL/6 mice that were subsequently received with a sub-lethal dose (6.75 Gy) of X-rays [3]. In the present study, we examined whether the similar radioadaptive response of bone marrow stem cells was observed when the mice were exposed to a low dose-rate (1 mGy/min) of pre-irradiation.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, the priming low-dose of X-rays also markedly reduced some of the other detrimental effects in the survivors. In the present mouse model for AR induction, the mechanisms responsible for rescue of bone marrow death are mainly of priming irradiation-induced radioresistance to the challenging irradiation-induced Trp-53 derived-apoptosis in hematopoietic stem cells (Horie et al, 2002;Okazaki et al, 2007). Recovery of blood platelet counts after exposure is one of the most important factors for restoration of bone marrow death (Takeda et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The mouse models for AR induction (Yonezawa, 1996) were with great reliability and reproducibility in different laboratories (Nose et al, 2001;Otsuka et al, 2008;). The induced AR could be generally divided into two phenotypes according to the attitude of the priming dose and the interval between the priming and challenging irradiation, involving different mechanisms: AR induced 2 weeks after a priming irradiation at a dose from 0.3 to 0.5 Gy was due to radioresistance occurred in blood forming tissues which was a Trp53 dependent event (Otsuka et al, 2008;Horie et al, 2002), and interaction between blood forming tissue and the central nervous system was thought to contribute to AR induced 2 months after a priming dose at 0.05 or 0.1 Gy (Yonezawa, 2000;Misonoh & Yonezawa, 1997). AR, as one of the most important phenomena in radiation biology, has been studied for nearly three decades, however, almost all the investigations at the whole body level were performed using low LET X-or gamma-irradiations for both priming and challenging doses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation